EFEKTIVITAS PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PEDESAAN (PNPM-MP) DALAM MENUNJANG PEMBANGUNAN PERTANIAN DI KECAMATAN NGAMBUR KABUPATEN LAMPUNG BARAT - Mutakin, Mutakin; Gitosaputro, Sumaryo; Adawiyah, Rabiatul (Jurnal Ilmu-Ilmu Agribisnis, 2013)
This study aims to determine (1) the effectiveness of rural community empowerment national program (PNPM-MP) and (2) factors related to the level of the effectiveness of the program in supporting agricultural development. Research was conducted in Ngambur sub district of West Lampung Regency from February to April 2012. Respondents were 68 farmers taken proportionally from 21 farmer groups. Method used was a descriptive analysis. The correlation between variables was tested using Rank Spearman correlation analysis. Result showed that the PNPM-MP was quite effective in supporting agricultural development in Ngambur Subdistrict of West Lampung Regency. The factors related to the level of the effectiveness in supporting agricultural development were the level of knowledge of the group members, the role of facilitator and district management team activities, and the amount of the PNPM-MP fund. The factor not related to the effectiveness of the PNPM-MP in supporting agricultural development in sub Ngambur West Lampung Regency was the level of participation of group members. Keywords: agricultural, effectiveness, independent, program, empowerment